The Political Regulation Wave A Case of How Local Incentives Systematically Shape Air Quality in China - Victoria Shen, Shiran (Social Sciences, 2022)
Why has there been uneven success in reducing air pollution even in the same locality over time? This book offers an innovative theorization of how local political incentives can systematically affect bureaucratic regulation and empirically examines the control of different air pollutants in China and - to a lesser extent - in Mexico.?